Invigorating Forest Governance by Gender Training - Pandey, Gopa (Indian Forester, 2017)
The forestry organizations are gearing up to meet the challenges of sustainable management of forest resources in allocated time and space. The capacity building during the last three decades has achieved colossal success so far knowledge of forestry, mechanical and electronic arenas are concerned. However, lacunae in a few gender communication and behavioral ecosystems, especially interpersonal and among cadres, needs refinement. The changing social constitution of the forestry sector, where people in general and gender equity in particular, calls for organizational development. In the past, small project driven capacity building in gender for the personnel was introduced largely addressing the inclusion of women in planning and decision making in joint forest management committee, which barely addressed appropriate development of gender perception of forestry personnel. The cognizance of gender redistributary attitude to be developed in human resource is imperative. Gender is to be internalized across all the cadres of the forest force. Specific training modules are developed addressing the gender training needs vis-a-vis their roles and responsibilities in the organization. These modules are focused to address the behavioral and communication ecosystems of Forest Guards, Forester and Deputy Range Officers, Range Officers, ACFs, DFOs and Conservators, CCFs and APCCFs and PCCFs. The framework for training is based on the allocated roles and responsibilities specific to present cadre. The enabling policies, principles and practices are used to exemplify the module with appropriate examples derived from nationwide experience. The framework will enable the forestry personnel to yield better results in achieving sustainable forest management without any social encumbrances, which often act as impediment to work output of the personnel.